2020
DOI: 10.20900/jpbs.20200006
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Pediatric Psychiatric Emergencies: A Health Systems Approach

Abstract: Less than half of African American youth with severe mental disorders receive psychiatric care. When they do receive care, African American youth use the Emergency Department at higher rates than whites. We examine whether rapid expansion of primary mental health care at Community Health Centers reduces Emergency Department visits for psychiatric care especially among African American youth. Through four studies, we examine (1) the impact of mental health service capacity on the disparity of psychiatric care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A systematic review of randomized controlled trials examined the impact on ED utilization of mental health care provided in outpatient, community, school, and primary care settings and concluded that there is limited evidence to suggest an effect (Kirkland et al, 2018 ). A related study found that increasing access among African Americans to community health center services produced a statistically significant, but practically insignificant reduction in racial and ethnic disparities in psychiatric ED visits (Das et al, 2020 ).…”
Section: Categories Of Informationmentioning
confidence: 99%
“…A systematic review of randomized controlled trials examined the impact on ED utilization of mental health care provided in outpatient, community, school, and primary care settings and concluded that there is limited evidence to suggest an effect (Kirkland et al, 2018 ). A related study found that increasing access among African Americans to community health center services produced a statistically significant, but practically insignificant reduction in racial and ethnic disparities in psychiatric ED visits (Das et al, 2020 ).…”
Section: Categories Of Informationmentioning
confidence: 99%